Peer support by interprofessional health care providers in aftermath of patient safety incidents: A cross‐sectional study. (9th May 2021) - Vanhaecht, Kris; Zeeman, Gerda; Schouten, Loes; Bruyneel, Luk; Coeckelberghs, Ellen; Panella, Massimiliano; Seys, Deborah; ,
Abstract: Aim: To investigate the health care professionals' preferences pertaining to support in the aftermath of patient safety incidents and potential variation thereof depending on the degree of harm. Background: Peer support systems are available to support health care professionals in the aftermath of patient safety incidents. It is unclear which type of support is best offered by whom. Methods: A cross‐sectional study in 32 Dutch hospitals. Results: In total, 2, 362 nurses and 1, 404 doctors indicated they were involved in patient safety incidents at any time during their career (86%). Less than 10% of health care providers had spoken with professional support, and less than 20% admitted a need to do so. They used different support. A higher degree of harm related to higher odds of desiring support. Respondents mainly wanted to understand what happened and how it can be prevented. Conclusion: The desired support of health care professionals in the aftermath of patient safety incidents depends on the level of harm. Implication for nursing management: Health care professionals seem to mostly rely on persons they are close with, and they mainly desire information related to the aftermath of patient safety incidents. This should be taken into account when support programmes are set up.